Pengaruh pengungkapan risiko lingkungan terhadap likuiditas dan biaya modal saham - Rizky Eriandani; I Made Narsa; Andry Irwanto (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to empirically examine the effect of environmental risk disclosure on the cost of equity and stock liquidity. Environmental risk disclosure is measured by content analysis based on the number of sentences in the annual or sustainability report. The research samples were 456 companies included in the high profile industry and were assessed by the Trucost database in 2013-2015. The data were processed using Eviews 10 run for panel least squares common effects method. The results show that environmental risk disclosure has a significant effect on stock liquidity, but does not have a significant effect on the cost of equity. The results of this study contribute to expand the disclosure theory, because it empirically proves that the environmental risk information used by investors.